2015
DOI: 10.1002/14651858.cd010981.pub2
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic-only versus prophylactic platelet transfusion strategy for preventing bleeding in patients with haematological disorders after myelosuppressive chemotherapy or stem cell transplantation

Abstract: We found low- to moderate-grade evidence that a therapeutic-only platelet transfusion policy is associated with increased risk of bleeding when compared with a prophylactic platelet transfusion policy in haematology patients who are thrombocytopenic due to myelosuppressive chemotherapy or HSCT. There is insufficient evidence to determine any difference in mortality rates and no evidence of any difference in adverse events between a therapeutic-only platelet transfusion policy and a prophylactic platelet transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 194 publications
(486 reference statements)
0
27
0
3
Order By: Relevance
“…A search of published literature was undertaken using the evidence from several systematic reviews that are either currently being undertaken by members of the writing group (Estcourt et al , ,b,c), or that have been recently published (Hedges et al , ; van Veen et al , ; Lieberman et al , ; Pavenski et al , ; Wardrop et al , ; Kumar et al , ; Vassallo et al , ; Crighton et al , ; Nahirniak et al , ). This was supplemented by searching PubMed and the United Kingdom Blood Transfusion Services (UKBTS)/Systematic Review Initiative (SRI) Transfusion Evidence Library (http://www.transfusionevidencelibrary.com) up to November 2014 using specific search terms relevant to each section of the guidelines.…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…A search of published literature was undertaken using the evidence from several systematic reviews that are either currently being undertaken by members of the writing group (Estcourt et al , ,b,c), or that have been recently published (Hedges et al , ; van Veen et al , ; Lieberman et al , ; Pavenski et al , ; Wardrop et al , ; Kumar et al , ; Vassallo et al , ; Crighton et al , ; Nahirniak et al , ). This was supplemented by searching PubMed and the United Kingdom Blood Transfusion Services (UKBTS)/Systematic Review Initiative (SRI) Transfusion Evidence Library (http://www.transfusionevidencelibrary.com) up to November 2014 using specific search terms relevant to each section of the guidelines.…”
Section: Scopementioning
confidence: 99%
“…Two of the included studies were recent large RCTs (Wandt et al , ; Stanworth et al , ), both of which showed that prophylactic platelet transfusions reduced the risk of bleeding when all patients with haematological malignancies receiving treatment (e.g. chemotherapy or transplantation) were considered (Crighton et al , ), but this effect was not seen in a pre‐specified sub‐group ‒ patients receiving autologous haematopoietic stem cell transplants (HSCT) (Table ) (Stanworth et al , ). This finding indicates that prophylactic transfusion should continue to be the standard of care in patients receiving intensive chemotherapy or allogeneic transplantation but may not be appropriate in low risk groups with short periods of thrombocytopenia.…”
Section: Prophylactic Transfusion Of Platelets To Patients With Thrommentioning
confidence: 99%
“…A systematic review synthesising the data from six trials of prophylactic platelet transfusion versus on demand transfusion for patients undergoing myelosuppressive chemotherapy or stem cell transplantation found that clinically significant bleeding was less common amongst patients treated with prophylactic platelet transfusions than those receiving on demand therapy (Crighton et al, 2015). A key question before considering alternatives to transfusion is whether prophylactic platelet transfusion is necessary at all.…”
Section: No Platelet Transfusionmentioning
confidence: 99%
“…A key question before considering alternatives to transfusion is whether prophylactic platelet transfusion is necessary at all. A systematic review synthesising the data from six trials of prophylactic platelet transfusion versus on demand transfusion for patients undergoing myelosuppressive chemotherapy or stem cell transplantation found that clinically significant bleeding was less common amongst patients treated with prophylactic platelet transfusions than those receiving on demand therapy (Crighton et al, 2015). (Afdhal et al (2014), Geissler et al (2003), Prica et al (2014), Zeng et al (2011) In clinical use in some types of thrombocytopenia.…”
Section: No Platelet Transfusionmentioning
confidence: 99%
“…A recent systematic review compared the use of prophylactic platelet transfusions with therapeutic‐only platelet transfusions in patients with haematological malignancies receiving chemotherapy or autologous HSCT . Overall, a therapeutic‐only platelet transfusion strategy was associated with an increased risk of clinically significant bleeding episodes and number of days with significant bleeding . However, bleeding risk varied between patient disease and treatment groups.…”
Section: Clinical Contextsmentioning
confidence: 99%